THE DEVELOPMENT OF STUDENTS WORKSHEET ORIENTED PROBLEM SOLVING TO TRAIN CREATIVE THINKING SKILLS IN ACID BASE MATTER FOR 11th GRADE (UNESA Journal of Chemical Education, 2019)
This research aims to produce student worksheet oriented problem solving to train creative thinking skills in an acid base matter for 11th grade that is feasible. Feasibility of student worksheet can be known from its validity, practicality, and effectiveness. Development of the worksheet refers to the Research & Development (R&D) model limited to the trial stage. The validity of the worksheet consists of content validity and construct validity. Content validity in worksheet 1, 2, and 3 have percentage respectively 88.00%, 88.00%, and 86.67%. Construct validity includes a linguistic, presentation, and graphics criteria. Result that got respectively for each worksheet 1, 2, and 3 for language criteria 86.67%, presentation criteria 87.78%, 87.78%, and 86.67%, graphical criteria 88.00%, 86.67%, and 86.67% with highly valid categories. The practicality of the worksheet is determined by the observation of students activities which got a percentage of 100% and students responses in terms of the criteria of content, linguistic, presentation, and graphics get the percentage of 98.33%, 100%, 98.00%, and 100%. The effectiveness of the worksheet in terms of increasing results of pretest and posttest in creative thinking skills for each student using the N-Gain Score formula and obtained the value <g>≥0.7 with high categories and for creative thinking classically obtained from the assessment of each component of creative thinking skills respectively for fluent and flexible thinking skills get the same percentage which is equal to 94% with very high categories while original and detailed thinking skills get the same percentage that is equal to 81% with a high category. The worksheet can be stated that feasible to use because it has fulfilled validity, practically, and effectiveness criteria. Keywords: students worksheet, creative thinking, problem solving, acid base.